2009
DOI: 10.2188/jea.je20080044
|View full text |Cite
|
Sign up to set email alerts
|

Subsite Distribution of Gastric Cancer in an Area of High Prevalence—Northwest Iran

Abstract: BackgroundThe aim of the present study was to determine subsites of gastric cancer in East Azerbaijan, Iran—a high incidence region for gastric cancer and Helicobacter pylori infection.MethodsData were collected from 2002 through 2007 from patients who sought treatment for gastrointestinal symptoms or signs at a university clinic and subsequently underwent upper gastrointestinal endoscopy.ResultsCancer was diagnosed and histologically confirmed in 362 patients (352 adenocarcinomas). The mean age of the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The bulk of evidence suggests the association between use of salt and salty foods (Marmot et al, 2005)with increase in gastric cancer. Besides, using fresh fruit especially citrus and vegetables (containing alliums and anti oxidant) (Matsuzaka et al, 2007;Bafandeh & Farhang, 2009),and fresh fish (Terry et al, 2001;Kim et al, 2004) have been mentioned by various studies as preventive factors of gastric cancer. Although the diet of Mediterranean and Middle Eastern countries include safe food like fresh vegetables and fish (Hossein, 2010), they have also turned to western foods and lifestyle in recent decades.…”
Section: Discussionmentioning
confidence: 99%
“…The bulk of evidence suggests the association between use of salt and salty foods (Marmot et al, 2005)with increase in gastric cancer. Besides, using fresh fruit especially citrus and vegetables (containing alliums and anti oxidant) (Matsuzaka et al, 2007;Bafandeh & Farhang, 2009),and fresh fish (Terry et al, 2001;Kim et al, 2004) have been mentioned by various studies as preventive factors of gastric cancer. Although the diet of Mediterranean and Middle Eastern countries include safe food like fresh vegetables and fish (Hossein, 2010), they have also turned to western foods and lifestyle in recent decades.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported an increasing trend for the incidence of stomach cancer in both males and females (20). Explanations for the increase in incidence include higher exposure to Helicobacter pylori (21), unhealthy diets, consumption of salty foods, and lower rates of consumption of fruits and fresh vegetables (22). Despite the gradual decline in the global mortality rates, stomach can-cer was a major cause of death in the present study for both males and females.…”
Section: Discussionmentioning
confidence: 56%
“…In this regard, spatial analyses help to generate new hypotheses. However, it is also important that clusters associated with certain cumulative risks such as income, urbanization and dietary patterns or areas that require the targeted interventions can be found (Bafandeh & Farhang, 2009;Hao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%